OS4.3 Feasibility and benefit of Molecular Profiling to Guide Enrollment of Patients with Recurrent Gliomas in Early Phase Trials. (6th September 2019) - Baldini, C; Younan, N; Castanon Alvarez, E; Bahleda, R; Hollebecque, A; Dhermain, F; Ammari, S; Alentorn, A; Dumont, S; Frenel, J; Di Stefano, A; Bielle, F; et al.
Abstract: BACKGROUND: Participation of glioma patients in early phase clinical trials has recently shown to be safe, although clinical benefits reported in this population were marginal. We aimed to evaluate whether an enrichment strategy based on molecular profiling associates with improved outcome in gliomas patients participating in early phase trials. MATERIAL AND METHODS: Records of patients enrolled in early phase trials of cytotoxic therapies, small molecule inhibitors or monoclonal antibodies from 2008 to 2017 were analyzed for clinicopathological characteristics, toxicity, response, median progression-free survival (PFS) and overall survival (OS). The primary objective was to evaluate the feasibility and benefit of using molecular profiling to guide enrollment. RESULTS: Ninety-one patients were enrolled, of whom 47/91 (51.6%) were molecularly oriented. Molecular targets included IDH1/2 (n=15) and BRAF (11) mutations, FGFR1-3 fusions (n= 10) and mutations (n = 4), mismatch repair deficiency (8), and MDM2 amplification (1). Grade 3/4 adverse events were reported in 9/91 (9.9%) patients. In patients with IDH1/2 -wild-type high-grade glioma (n=45), the overall response rate (24.0% [95% CI 11.5–43.4] vs 0.0% [95% CI 0.0–16.1], P =0.027) was significantly higher in molecularly-oriented vs non-molecularly-oriented patients. Updated outcome results, and clinical and molecular factors associated with response, PFS and OS in multivariate analyses will be presented at the conference. CONCLUSION: Using molecular profiling to guide enrollment in early phase trials is feasible and offers potential benefit to gliomas patients. Further studies are warranted to identify the population most likely to benefit from this approach.